Human Resource Development Management : Systematic Literature Riview (SLR) - Fian Arifiona Faradila; Sopiah Sopiah (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The purpose of this SLR is to analyze the application of human resource development in the work environment. The method used in this research is the PRISMA (Preferred Reporting Items for Systematic Review) method. Data sources obtained from Science Direct and Google Scholar for the 2019-2023 period. The results obtained were 236 journals, then data reduction was carried out using inclusion and exclusion criteria, resulting in 11 journals that would be reviewed. The results of this study literature review show the priority of the role and tasks of human resource development in increasing productivity. So that human resource development has a good impact on the company and the employees themselves.